The Influence of Entrepreneurial Characteristics of Arabica Coffee to Business Performance Farmer’s In Karo Regency - Elvin Desi Martauli; Lasma Melinda Siahaan (JASc (Journal of Agribusiness Sciences), 2019)
Coffee farming opportunities, if well developed, will have an impact on increasing business performance. One of the efforts that can be done is building quality human resources based on entrepreneurial characteristics. Entrepreneurial characteristics are thought to have a significant influence on the occurrence of farm performance improvement. The purpose of this study was to analyze the characteristics of entrepreneurship, the performance of coffee farming and analyze the effect of entrepreneurial characteristics on the performance of Arabica coffee farming in Karo Regency Respondents used as the sample of this study were taken using cluster random sampling techniques from three districts with a total of 120 respondents of Arabica coffee farmers. The analytical tool used in this research is descriptive analysis and Partial Least Square (SEM-PLS). The results of research on farm performance variables are significant and positive influenced by the characteristics of entrepreneurship. Variable characteristics that have a positive effect are experience, desire to do business, perception and courage to take risks. The most dominant characteristic of entrepreneurship is the desire to do business, but overall it can be said to be strong.